2013
DOI: 10.3904/kjim.2013.28.2.231
|View full text |Cite
|
Sign up to set email alerts
|

A case of secondary syphilis presenting as multiple pulmonary nodules

Abstract: Syphilis is a sexually transmitted disease caused by Treponema pallidum. The prevalence of this disease has recently increased worldwide. However, pulmonary involvement in secondary syphilis is extremely rare. A 51-year-old heterosexual male patient presented with multiple pulmonary nodules with reactive serology from the Venereal Disease Research Laboratory test and positive fluorescent treponemal antibody absorption testing. A hematogenous metastatic malignancy was suspected and an excisional lung biopsy was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…2 Pulmonary lesions appear as an infiltration, 3 consolidation with pleural effusion, 32 solitary pulmonary nodule, 33 or multiple ill-defined nodules. 34 Kim et al 35 reported the third case of secondary syphilis, presenting as multiple pulmonary nodules, and this was the first report in Korea. The importance of this issue is that well-defined pulmonary nodules could mimic hematogenous metastatic carcinoma.…”
Section: Pulmonary Nodulesmentioning
confidence: 88%
“…2 Pulmonary lesions appear as an infiltration, 3 consolidation with pleural effusion, 32 solitary pulmonary nodule, 33 or multiple ill-defined nodules. 34 Kim et al 35 reported the third case of secondary syphilis, presenting as multiple pulmonary nodules, and this was the first report in Korea. The importance of this issue is that well-defined pulmonary nodules could mimic hematogenous metastatic carcinoma.…”
Section: Pulmonary Nodulesmentioning
confidence: 88%
“…The differential diagnosis for pulmonary involvement in patients with syphilis is extensive and includes primary and metastatic lung cancer, lymphoma, fungal infection, tuberculosis, septic embolism, pulmonary infarction, sarcoidosis, rheumatoid nodules, and vasculitis 2,6 . While microbiological diagnosis of syphilis in these cases is difficult, transbronchial biopsy, open lung biopsy, bronchial lavage, immunohistochemistry, and polymerase chain reaction may reveal the presence of Treponema pallidum 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, pulmonary involvement in secondary syphilis is extremely rare [2,3]. To our knowledge, only seven cases of secondary syphilis with pulmonary involvement including CT findings have been published in the English-language literature.…”
mentioning
confidence: 90%